Challenges of life after school in Malaysia - Zainol Rashid, Azra; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2024)
In this increasingly sophisticated world, the challenges of life among students immediately after graduation, whether SPM, pre-university, or university, for the sake of their survival is important to be studied and highlighted. Previous studies that touched on facing the challenges of Student Life After finishing secondary school were not conducted comprehensively, thus jeopardizing the ongoing efforts to produce Malaysians who are capable of achieving personal well-being, as well as contributing to the harmony and prosperity of families, communities, and countries as enshrined in the National Education Philosophy. The research methodology employed in this study is done by searching, selecting, and analyzing literature sources such as journals and books to understand and summarize information and findings relevant to the topic of study. The results of the study found that there are three themes or aspects of the challenge. The three themes are academic, career, and life aspects, which can be elaborated into 13 life challenges that post-secondary students must face. Therefore, serious attention should be paid to how to prepare citizens who can express the spirit of the National Education Philosophy to the maximum.